Selection biases in observational studies affect associations between 'moderate' alcohol consumption and mortality. (17th June 2016) - Naimi, Timothy S.; Stockwell, Timothy; Zhao, Jinhui; Xuan, Ziming; Dangardt, Frida; Saitz, Rich; Liang, Wenbin; Chikritzhs, Tanya
Abstract: Selection biases may lead to systematic overestimate of protective effects from 'moderate' alcohol consumption. Overall, most sources of selection bias favor low‐volume drinkers in relation to non‐drinkers. Studies that attempt to address these types of bias generally find attenuated or non‐significant relationships between low‐volume alcohol consumption and cardiovascular disease, which is the major source of possible protective effects on mortality from low‐volume consumption. Furthermore, observed mortality effects among established low‐volume consumers are of limited relevance to health‐related decisions about whether to initiate consumption or to continue drinking purposefully into old age. Short of randomized trials with mortality end‐points, there are a number of approaches that can minimize selection bias involving low‐volume alcohol consumption.